PENETAPAN KADAR FLVONOID EKSTRAK ETANOL BIJI ALPUKAT (Persea americana Mill.) DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-Vis - RISMA, WA ODE; Abidin, Zainal; Rahmawati, Rahmawati (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
Avocado (Persea americana Mill.) is a plant that can thrive in tropical areas such as Indonesia. The use of avocado (Persea americana Mill.) as a medicinal plant has been widely used. People usually use avocado seeds as traditional medicine. Avocado seeds (Persea americana Mill.) are plants that contain flavonoid compounds. This study aims to determine the levels of flavonoids in the ethanol extract of avocado (Persea americana Mill.) seeds using the UV-Vis spectrophotometry method. This research was conducted experimentally with qualitative and quantitative methods using UV-Vis spectrophotometry. The results showed that the average flavonoid content of the ethanol extract of avocado seeds was 46.953 mgQE/g extract.